DESCRIPTION OF ACCIDENT AT STEEL INDUSTRY IN GRESIK INDONESIA - Ratih Damayanti; Egy Ramandhani (Universitas Darussalam Gontor, 2018)
One of the main causes of loss in the company or industry is an occupational accident. The loss were losing work time, companies spend a lot of money to do the treatment to the victim or the cost for damages that arise. Industri Baja X Gresik aas one of the largest steel processing industry in Indonesia has potential hazards that can lead to work accidents. The aim of this research was to know the description of work accidents in Industri Baja X Gresik including the characteristics and history of accidents workers. This research was descriptive observational research conducted to crossectional approach. The respondent of this study were the total population of workers who had experienced occupational accidents from September 2016 to August 2017. Most of the workers (55%) from 4 units of work have experienced accidents such as scratched, cut or slashed. The most dominant factor were the unsafe behavior (55%) and the unsafe condition (20%). Conclusion : The work accident that happened in Industri Baja X Gresik in consequence of unsafe act and unsafe condition. Eventhough not a fatal accident if an accident then the main cause should be eliminated. Recommendation : The Company should take prevention with adequate use of PPE, the implementation of 5 R and control of production space and safety promotion activity to increase worker knowledge and awareness in order to decrease accident rate for worker with age group below 45 years. Keywords : accidents, metal industry, Indonesia